NEW CONCEPTS IN HEPATIC ECHINOCOCCOSIS - Umarova T. A.; Kudratova Z. E.; Muxiddinova G. (Web of Journals Publishing, 2024)
Echinococcosis of the liver is one of the most common parasitic diseases, which is based on the formation of cysts in the liver. The main signs of this pathology are general weakness, significant decrease in appetite, decrease in body weight, feeling of heaviness in the liver region, nausea after eating fried or fatty food, stool disorder. To diagnose liver echinococcosis, general blood tests, immunologic methods, abdominal ultrasound, magnetic resonance imaging, liver SPECT, laparoscopy, etc. are used. The most effective treatment is surgical excision of cysts; antihelminthic drugs are also used.
Keywords: Hepatic echinococcosis, parasitic infection, tapeworm, liver.